Intellectual Pilgrimages and Local Norms in Fashioning Indonesian Islam = Pélerinages intellectuels et normes locales dans la mise en forme de l’islam indonésien - Bowen, John Richard (Revue des mondes musulmans et de la Méditerranée, 2008)
Muslims living in the Indonesian archipelago have long placed considerable importance on their travels to and communications with what they saw as intellectual centers for the study of Islam. I trace some of the effects of these “intellectual pilgrimages” to Mecca, Cairo, and elsewhere on Indonesian deliberations about Islam, particularly concerning Islamic law. I argue that these references to abroad do not flatten out global Islamic discourse, but often stimulate an attention to local norms, or an effort to justify Islamic law as stemming from local traditions.